Pengaruh Audit Tenure, Audit Delay, Ukuran Perusahaan, Dan Independensi Terhadap Kualitas Audit Pada Perusahaan Manufaktur Sub Sektor Pabrik Kelapa Sawit Yang Terdaftar Di Bursa Efek Indonesia Periode 2022-2024 (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The researchers sought to answer the question, "What aspects impact audit quality?" by looking at aspects such as the duration of auditor involvement, audit delays, company size, and independence. Using quantitative research methods, the study surveyed 66 organizations over three years, with 22 of them meeting the requirements for inclusion in the sample. The multiple linear regression method was applied to the data of this study. Targeted sampling, which seeks to establish the sample size according to predetermined standards, is the sampling method used. The duration of auditor involvement and independence had no effect on audit quality, but audit delays and company size had an effect.
Keywords: Audit Tenure, Audit Delay, Company Size, and Independence to Audit Quality